Political Economy Dilemma of UNASUR Member Countries - Gilang Rizki Aji Putra; Nur Rohim Yunus; Atep Abdurofiq (BULETIN ADALAH, 2023)
This article discusses the political-economic challenge facing UNASUR members. The regional integration forum UNASUR promotes political, economic, and social cooperation in South America. This institution has encountered tremendous challenges in recent years, primarily due to global economic forces and clashing internal political agendas. This article examines how economic issues like commodity reliance and macroeconomic volatility affect internal politics in each country using policy analysis. This political economic problem hinders UNASUR's integration and regional stability. This study also shows how external actors and international interactions affect UNASUR's political-economic processes. Finally, to help UNASUR achieve regional integration and sustainable development in South America, this paper proposes numerous policy changes.